Fashionopolis: The Price of Fast Fashion and the Future of Clothes - Dana Thomas (UK Head of Zeus, 2019)
An investigation into the damage wrought by the colossal clothing industry - and the grassroots, high-tech, international movement fighting to reform it. 'A gripping blockbuster ... Thomas researches meticulously and writes with simmering even-handed anger' TELEGRAPH. Fashionopolis is the definitive book on the cost of fast fashion, and a blueprint for how we get to a more sustainable future. Fashion has blighted our planet. Today, one out of six people on earth work in fashion, churning out 100 billion garments a year. Yet 98 percent of them do not earn a living wage, and 2.1 billion tonnes of clothing is thrown away annually. The clothing industry's exploitation of fellow humans and the environment has reached epic levels. What should we do? Bestselling author and veteran journalist Dana Thomas has travelled the globe to find the answers. In Fashionopolis, she details the damage wrought by fashion's behemoths, and celebrates the visionaries - including activists, artisans, designers, and tech entrepreneurs - fighting for change. We all have been casual about our clothes. It's time to get dressed with intention. Fashionopolis is the first comprehensive look at how to start.
Keywords: Nonfiction; Fashion; Environment; Sustainability; Business; Economics; History; Politics; Climate change; (EXD 300) Design Major Final Portfolio